Partially involuting congenital hemangioma - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Detected in the mid-1990s, congenital hemangioma does not prevail in the female sex; it can be highlighted with prenatal ultrasound, is present at birth already fully developed and has no receptors for GLUT1. Clinically, it is characterized by greater size than infantile hemangioma, a grayish color, no growth in post-natal period and above all in many cases rapid regression within a few months, justifying the name of rapidly involuting congenital hemangioma (RICH). It was then realized that not all the congenital hemangiomas rapidly involute, some of them being still present after one year of life; non involuting congenital hemangioma (NICH) do not regress even in the times of infantile hemangioma. The latter, which often have superficial telangiactases, can be three-dimensional, plaque or even non-infiltrated patches. They may not at all regress or partially regress (PICH) as in the actual case.